2018
DOI: 10.21608/jenvbs.2018.4421.1031
|View full text |Cite
|
Sign up to set email alerts
|

Potential of some plant extracts in controlling wheat leaf rust caused by Puccinia triticina Eriks.

Abstract: Plant extracts are among the biological control agents that directly affect the plant pathogens and can induce resistance in plants against phytopathogens (Mishra and Raja 1999). Recently, plant extracts have gained considerable attention as alternative options to synthetic fungicides and efforts have been made to utilize these extracts in the control strategies against plant diseases (Srivasata et al. 2011; Elsharkawy and El-Sawy 2015). It has been previously proven that plant extracts are effective control a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The suggested strategy used in this case may by the production of siderophores leading to iron starvation which affect pathogen growth. Previous studies have demonstrated that Trichoderma species can be used as a biocontrol agent in controlling a number of plant diseases with high efficacy (Kucuk and Kivanc 2003;Omara et al 2017Omara et al , 2018Elkhwaga et al 2018). Also, the light microscope image illustrates the possible mechanism used by the Trichoderma to inhibit fungal growth where the affected pathogen mycelia appeared empty from cytoplasm and its component in addition to loss of septation, so it is likely that the mechanism involved in this case is related to the hydrolytic enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The suggested strategy used in this case may by the production of siderophores leading to iron starvation which affect pathogen growth. Previous studies have demonstrated that Trichoderma species can be used as a biocontrol agent in controlling a number of plant diseases with high efficacy (Kucuk and Kivanc 2003;Omara et al 2017Omara et al , 2018Elkhwaga et al 2018). Also, the light microscope image illustrates the possible mechanism used by the Trichoderma to inhibit fungal growth where the affected pathogen mycelia appeared empty from cytoplasm and its component in addition to loss of septation, so it is likely that the mechanism involved in this case is related to the hydrolytic enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…The potential of these oils can be related to the activity of many ingredients such as phenols, thymol and carvacrol. Several studies (Carmo et al 2008;Gallucci et al 2014;Fayaz et al 2017;Shabana et al 2017;Elkhwaga et al 2018) considered phenol compounds as the most effective ingredient with the highest antifungal activity among all terpene compounds of essential oils. The suggested mechanism is that monoterpene alcohols disrupt the permeability of the fungal plasma membrane and inhibit the respiration process on mitochondrial membrane (Cox et al 2000;Deba et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Abdallah et al (2019) found that marjoram essential oil controlled wilt cumin disease. Essential oils can be related to the activity of many components such as phenols, thymol and carvacrol (Carmo et al, 2008;Gallucci et al, 2014;Fayaz et al, 2017;Shabana et al, 2017 andElkhwaga et al, 2018). The suggested mechanism is that monoterpene alcohols disrupt the permeability of the fungal plasma membrane and inhibit the respiration process on mitochondrial membrane (Cox et al, 2000 andDeba et al, 2008).…”
Section: Results Presented In Tablesmentioning
confidence: 99%
“… In an in vivo experiment (greenhouse assay), all plant extracts decreased the disease severity of wheat leaf rust. [ 44 ] Olea europaea (leaves) Capsicum annuum (fruits) Seed borne fungi (sorghum grains disease) Aqueous extract obtained by maceration of O. europaea leaf and C. annuum fruit were found effective in reducing incidence of seed-borne fungi. [ 45 ] Eucalyptus globulus (leaves) Calotropis procera (leaves) Melia azedarach (leaves) Datura stramonium (leaves) Acalypha indica (leaves) Alternaria alternata Rhizopus spp.…”
Section: Crude Extracts From Plants As Fungicides Against Phytopathog...mentioning
confidence: 99%